(untitled) (Research, Society and Development, 2020)
Animals are currently considered to be members of families. Thus, community awareness of responsible ownership associated with public policies is a fundamental point for the promotion of animal welfare and, consequently, of families. With this, the project of teaching, research and extension in medical clinic of small animals of the Federal University of Pelotas (ClinPet –UFPel) carried out extension activities, with the purpose of guiding and clarifying the population on topics related to the health of dogs and cats, it also sought to understand the guardians’ understanding of responsible guarding and animal welfare, as well as their needs and interests. Then, content disclosures, lectures, Quiz were carried out through social networks, a field survey was also carried out through the application of an online questionnaire. Instagram has increased the number of followers by almost 500%, currently having approximately 3700 followers. Through the questionnaire it was possible to understand that these users are a public concerned and interested in the well-being of their pets. In the Quiz, a total of 15,123 views were registered, generating a high rate of interaction. In the same context, the lectures promoted updating of the participants and provided an exchange of experiences between the speakers and spectators. In conclusion, the extension actions carried out for dog and cat guardians are of great importance and social networks were essential in the continuing education not only of the students who create the content, but also those who are interacting.